Health risk of some metals in maize grains cultivated close to Gosa and Gwagwalada solid waste dumpsites - Ogu, Gideon; O. Ojiego, Beatrice; Bello, Zainab; Josephine, Madu; E. Audu, Kalen; A. Abdullah, Shauibu; Gadzama, Ibrahim M. K.; Bolorunduro, Paul (LPPM Universitas Andalas, 2022)
Maize is a vital nutritional cereal for the infants, young children and adults. The environment which they are cultivated in Africa could expose to metal accumulations from soils, thereby posing health risks to the consumers. The objectives of this study were determine metal accumulations in maize grains (Zea mays L.) cultivated close to Gosa and Gwagwalada solid waste dumpsites and their health risks via consumption. A total of 36 soil samples (12 each from dumpsite soil, farmland soil and maize grains) were collected and analyzed for some metals [cadmium (Cd), lead (Pb), zinc (Zn), cobalt (Co), copper (Cu), chromium (Cr), nickel (Ni) and mercury (Hg)] using standard atomic adsorption spectrophotometer. The transfer factors and metal health risks in adults (60 kg; 22-48.9 years), young children (35 kg; 6-15 years) and infants (15 kg; 1-6 years) were evaluated using mathematical models. The ranges of metal (mg/kg) detected were 10114.00 to 0.52, 10.45 to 0.001 and 13.62 to 0.001 for dumpsite, farmland and maize grains, respectively. Though, within FAO/WHO and EU safe limits, Zn was significantly (p<0.05) highest in both locations, while Cd, Cr and Hg (0.001 mg/kg) were the least. Only Zn had transfer factor value below 0.5, which indicates possibilities of anthropogenic elevations. The estimated daily intake from consumption of maize grains (57 g) were generally high for Zn and low for Ni, Cd, and Hg in exposed individuals. The hazard index was below 1, which indicates no significant non-carcinogenic risks in exposed populations. The incremental lifetime cancer risks was below 10-6 and this suggest potential lifetime cancer risks in the order infants ? children ? adults. This study concluded that daily consumption of maize cultivated closed to dumpsites poses potential lifetime cancer concern and thus maize farming around dumpsites needs to be discouraged for safety reasons.